Spectrophotometric determination of thymol in pharmaceuticals with Gibb's reagent - Usra. Al-Neaimy (College of Education for Pure Sciences, 2009)
Abstract A simple and rapid spectrophotometric method for the determination of thymol in pure form and in pharmaceutical preparations is described .The method is based on the color reaction between thymol and 2,6-dichloroquinone-4- chloroimide (Gibb's reagent) in borate buffer medium (pH 10) to form a blue indophenol dye with maximum absorption 605 nm. Beer's law is obeyed over the concentration range of 0.04-16 μg. ml−1with a molar absorptivity of 18430 l. mol.cm−1and sandell sensitivity index of 0.008 μg.cm. The results obtained were both precise (RSD) better than 1% and accurate (average recovery) 100.50%. The method does not resort to temperature control or to solvent extraction .The method has been applied further, successfully to the determination of thymol in mouthwashes and the results obtained are comparable with those given by the standard 4-aminoantipyrine method.